The Implementation of Profit Sharing at Lembaga Perkreditan Desa - Ni Made Sri Ayuni; Ni Wayan Novi Budiasni (Universitas Pendidikan Ganesha, 2020)
Avoiding distortion of LPD funds requires transparency of financial reports and revenue sharing. Given that there are still frequent irregularities in the use of funds by the organizers. The purpose of this study was to determine the implications of financial performance and transparency on profit sharing. This research used quantitative methods from a population of 142 selected 60 samples. The data were collected by distributing questionnaires and collecting data on the number of samples in this study as many as 60 LPDs selected based on the stratified random sampling method. This study was analyzed using SEM (Structural Equation Modeling) analysis techniques with the PLS (Partial Least Square) method. Based on the first hypothesis, it shows that the relationship between financial performance variables and profit sharing shows the parameter coefficient value of 0.137 with a t value of 1.350. This value is smaller than the t table (1,960). The results of testing the second hypothesis indicate that the relationship between the transparency variable and profit sharing shows the parameter coefficient value of 0.724 with a t value of 8.179. This value is greater than the t table (1,960). Based on the research results, it can be concluded that financial performance has a positive relationship with profit sharing, and transparency has a positive relationship with profit sharing.